The HER2-binding affibody molecule (Z(HER2∶342))₂ increases radiosensitivity in SKBR-3 cells. - Lina Ekerljung; Johan Lennartsson; Lars Gedda (PLoS ONE, 2012)
We have previously shown that the HER2-specific affibody molecule (Z(HER2∶342))₂ inhibits proliferation of SKBR-3 cells. Here, we continue to investigate its biological effects in vitro by studying receptor dimerization and clonogenic survival following irradiation. We found that (Z(HER2∶342))₂ sensitizes the HER2-overexpressing cell line SKBR-3 to ionizing radiation. The survival after exposure to (Z(HER2∶342))₂ and 8 Gy (S(8Gy) 0.006) was decreased by a factor four compared to the untreated (S(8Gy) 0.023). The low HER2-expressing cell line MCF-7 was more radiosensitive than SKBR-3 but did not respond to (Z(HER2∶342))₂. Treatment by (Z(HER2∶342))₂ strongly increased the levels of dimerized and phosphorylated HER2 even after 5 minutes of stimulation. The monomeric Z(HER2∶342) does not seem to be able to induce receptor phosphorylation and dimerization or sensitize cells to irradiation.